Specific energy consumption of native starch industry in Thailand - Kriengkrai Assawamartbunlue; Wanwiwa Luknongbu (Energy Reports, 2020)
According to the Thai Energy Efficiency Plan (EEP 2015), the government has set the target of 30% reduction in 2036 compared to the total energy consumption in 2010. The industry sector accounts for approximately 37% of the total energy consumption. Thai industries have been classified into 11 main sectors, in which food, beverage, and tobacco are the most energy-consumed sectors which consume about 35.7% of the total energy consumption. Among industries in the food, beverage, and tobacco sector, the native starch industry is the second most energy-consumed industry. Thus, the rational amount of energy saving target will be assigned to the native starch industry. Their baseline energy consumption and their potential energy saving should be known to verify the actual amount of energy savings each year. In this paper, 18 of 67 native starch plants are carefully investigated and audited to determine baseline energy consumption (BEC) and specific energy consumption (SEC) based on plant performance. Factors that effect on BEC and SEC are identified. Equations for predicting baseline BEC and SEC are developed using statistic regression approaches. It is found that SEC and BEC of the native starch industry depend on annual production quantity and annual production hours. The regression equations for predicting baseline BEC and SEC are developed and are in ±10% error range of observed data.
Keywords: 330; Baseline energy consumption; Cassava; Energy performance index; Native starch; Specific energy consumption